Cortisol levels in beluga whales (Delphinapterus leucas): Setting a benchmark for Marine Protected Area monitoring - Loseto, Lisa L.; Pleskach, Kerri; Hoover, Carie; Tomy, Gregg T.; Desforges, Jean-Pierre; Halldorson, Thor; Ross, Peter S (Arctic science, 2018)
Beluga whales (Delphinapterus leucas) are facing profound changes in their habitat, with impacts expected at the individual and population level. Detecting and monitoring exposure and response to environmental stressors is necessary for beluga conservation and management of human activities. Cortisol has proven as a useful tool to assess stress on wildlife. Cortisol was measured in three blubber layers and plasma in subsistence-hunted beluga whales from the summers of 2007 to 2010 using an HPLC/MS/MS. We assessed the effect of biological and biochemical factors. Cortisol ranged from undetectable to 17.8 ng/g in blubber and 2.5 to 61.2 ng/mL in plasma. Concentrations were highest in the inner blubber layer likely reflecting circulating levels. All tissues were significantly higher in 2008 for reasons that remain unclear. Cortisol levels were on par with resting levels in captive belugas. Best fit models for cortisol revealed age to be an important determinant along with length and blubber thickness. Lack of relationships with biochemical factors such as organic contaminants suggests current cortisol levels are not significantly influenced by present contaminant concentrations. Our findings support the use of middle and outer blubber tissues for an integrated measure of chronic stress that are less subject to the influence of acute stress.